Suspense and Surprise in Media Product Design: Evidence from Twitch - Simonov, Andrey; Ursu, Raluca M.; Zheng, Carolina (Journal of Marketing Research, 2023)
The authors quantify the relative importance of beliefs-based suspense and surprise measures in the entertainment preferences of viewers of Twitch, the largest online video game streaming platform. Using detailed viewership and game statistics data from broadcasts of tournaments of a popular video game, Counter-Strike: Global Offensive, the authors compute measures of suspense and surprise for a rational viewer. They then develop and estimate a stylized utility model that underlies viewers’ decisions to both join and leave a game stream. The method used enables the authors to causally identify the direct effect of suspense and surprise on viewers’ utilities, separating it from other sources of entertainment value (e.g., team skill) and from indirect/supply-side effects (e.g., word of mouth, advertising). The authors show that suspense enters a viewer's utility but find little evidence of the effect of surprise. The magnitudes imply that a one-standard-deviation increase in round-level suspense decreases the probability of leaving a stream by .27 percentage points. The authors find no detectable effect of suspense and surprise on the decision to join a stream, ruling out indirect effects. Variation in suspense levels explains 9.2% of the observed range of the evolution of a stream's viewership. The authors use these estimates to evaluate counterfactual game and platform designs. They show that historical updates to Counter-Strike: Global Offensive game rules have increased tournament viewership by 4.1%, that rules can be further modified to increase viewership, and that alternative platform designs that inform joining users of games’ scores will additionally increase overall viewership by 1.3%. Together, these results illustrate the value of the authors’ method as a general tool that content producers and platforms can use to evaluate and design media products.